Role of Transition Metal-Hydroxide (M-OHx, M=Mn, Fe, Ni, Co) Co-catalyst Loading : Efficiency and Stability of CdS Photoanode. Issue 1776 (2015) - Pareek, Alka; Paik, Pradip; Borse, Pramod H.
ABSTRACT: In this work we have synthesized the colloidal particles of transition metal-hydroxide (M= Ni, Co, Mn, Fe) by a simple chemical precipitation method. The surface of spray deposited CdS thin films were modified using nano-colloids to utlize them as water oxidation catalysts (WOC) for the photoelectrochemical cell (PEC). A systematic comparison of the PEC performance of modified and unmodified film is carried out to understand the role of co-catalyst . Ni(OH)2 modification yields 3.4 times higher photocurrent density than bare CdS photoanode, and exhibits hydrogen-evolution rate of 600 μmol/hr. Fe(OH)2 modified film shows best stability of 8 hours as compared to the others.